Microstructure and tensile properties of 6061 aluminum alloy prepared by friction rolling additive manufacturing - Yan Ji; Li Zhang; Qing Dong; Xiping Song; Bin Yang (Journal of Materials Research and Technology)
Ring-shaped components, as critical parts in the aerospace industry, require further optimization of their forming methods. In this study, Friction rolling additive manufacturing (FRAM) technique was employed to successfully fabricate a ring-shaped 6061 aluminum alloy component. A systematic study was conducted on the microstructure, tensile properties and formation mechanism of the component along the build direction. The results showed that the component fabricated by the FRAM exhibited a uniform hardness distribution, with an average hardness of 64.1 ± 5.9 HV. The ultimate tensile strength (UTS) was 208 ± 4.3 MPa, and the yield strength (YS) was 97 ± 4.2 MPa, significantly higher than those of the base material (UTS: 128 ± 4.9 MPa, YS: 59 ± 4.1 MPa). The elongation of the FRAM-6061 alloy was 29.4 ± 3.3%, which is similar to that of the base material (30.8 ± 1.8%). During the additive manufacturing process, the repeated stirring action of the rotating tool facilitated the formation of a microstructure with an average grain size of 5.2 μm at the interlayer and 22.8 μm within the layers. The back stress strengthening mechanism generated by this microstructure is suggested to be the fundamental reason for the excellent coordination of strength and ductility in the FRAM-6061 aluminum alloy.